Tristán Roca Suárez e sua atuação na Guerra Grande : ecos do labor intelectual de um desterrado (1866-1868) - Silva, Leonam Lauro Nunes da (2020)
The biggest military event ever occurred in South America, in XIX century, retains a number of questions on some issues discussed. One is the impact of that in South America, especially in countries bordering the belligerents. Bolivia then emerges in this study, bringing some characters hidden by historiography. Born in Santa Cruz de la Sierra in eastern Bolivia, Tristán Roca Suárez played a decisive role in the resistance undertaken by the Paraguayans throughout the conflict. However, did not the conventional way, through the weapons. Far from a military profile, the protagonist, intellectual, engaged in favor of Paraguayan cause through a relevant journalistic production, responsible for disseminating ideas through texts and images. Explained in the pages of the periodical "serious-humorous" entitled "El Centinela", these influenced the conduct of the actions during the war. Moreover, along the historic route, they constituted the "raw material" for the construction of a speech, assimilated by society, and fueled the construction of a paraguayan national identity.